HUBUNGAN PENGETAHUAN MENGENAI COVID-19 DENGAN PERILAKU CUCI TANGAN PAKAI SABUN SEBAGAI UPAYA PREVENTIF COVID-19 PADA SISWA SEKOLAH CALON TAMTAMA DI KEHIDUPAN BERASRAMA RINDAM JAYA TAHUN 2022 - Deandra Atya Maharani (2023)
COVID-19 is a respiration disorder that has experienced extensive spread throughout the world which has an impact on increasing morbidity and mortality, one of which is in Indonesia. One of the preventive measures to minimize the transmission of COVID-19 infection that is easy and affordable that can be implemented by the wider community is the behavior of Handwashing With Soap (CTPS). Boarding institution-based institutions such as the Tamtama Candidate School (SECATA) in the Kodam Main Regiment (Rindam) allow extensive transmission of infectious diseases between students. This study aims to analyze the relationship between knowledge about COVID-19 and CTPS behavior in SECATA students in Rindam Jaya in 2022. This study is a quantitative study of cross-sectional studies with a sample of 140 using a simple random sampling type probability sampling technique. The test used to perform bivariate analysis is the Fisher's Exact Test. The results showed the majority of respondents had less knowledge (n= 129, 92.1%) and the CTPS behavior of most respondents was good (123, 87.9%). Bivariate analysis using Fisher's exact test resulted in a p-value = 1,000 so that there was no significant relationship between knowledge about COVID-19 and CTPS behavior in SECATA Rindam Jaya students in 2022. Based on the results of the study, it was found that increasing knowledge about COVID-19 was not accompanied by an increase in CTPS behavior.